PIDANA NIHIL DALAM PERKARA TINDAK PIDANA KORUPSI PADA PT. ASABRI (Persero) (STUDI KASUS PUTUSAN NOMOR: 49/PID.SUS-TPK/2021/PN JKT.PST) - Elvini Tiara Putri (2023)
This study aims to find out and analyze the considerations of the judges who decided on a zero sentence against a corruption case involving the management of PT ASABRI (Persero) and a money laundering crime committed by Benny Tjokrosaputro, in his consideration that the counterclaim was deemed incompatible with social demands. justice and victims of acts that harm the state, judges are considered to only use the concept of procedural justice, not from the point of view of substantive justice. The research method used is Normative Juridical because the method used is guided by basic legal materials, realized by studying theories, concepts, legal principles and regulations related to this research regarding Zero Crimes in Corruption Crime Cases at PT ASABRI (Persero) (Case Study Decision Number: 49/Pid.Sus-Tpk/2021/Pn Jkt.Pst) and understand the problem while maintaining or relying on the field of law or research by applying normative juridical methods. The results of this study are to explain the judge's considerations in deciding the PT ASABRI (Persero) case by using Article 67 of the Criminal Code, in addition to contradicting the legal principle, namely lex specialis derogat lex specialis generalis which applies in the law on corruption in the a quo case, nor does this article strictly applies to criminal acts committed in accumulation in separate cases.